Artificial colored sand and preparation method thereof
By using raw materials such as aqueous acrylic resin, polyacrylamide modified dyes, etc., the color uniformity and wear resistance of artificial sand are improved through cross-linking and bonding effects, and the color color of artificial sand in the prior art is solved. The problems of unevenness and insufficient wear resistance achieve higher color fastness and service life.
Patent Information
- Application Number
- CN202411856059.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-14
AI Technical Summary
During the dyeing process, existing artificial colored sand can easily affect the color permeability, color fastness and color uniformity of the surface of quartz sand, and are easily worn in high-flow areas, resulting in color scraping and affecting service life.
Dyeing solution is prepared using raw materials such as aqueous acrylic resin, polyacrylamide modified dye, polycaprolactone envelope thickening agent, etc., to improve color uniformity and fastness through cross-linking and connection effects, and to use silane coupling agent and plasticizer Promote the dyeing layer to stabilize bond with quartz sand and improve wear resistance.
It has achieved the improvement of wear resistance, color fastness and uniformity of artificial colored sand, extended its service life, and maintained good color fastness under rainwater erosion conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of dyeing and processing of inorganic materials, and more specifically, to an artificial colored sand and a preparation method thereof. Background Art
[0002] Artificial colored sand is a kind of colored quartz sand obtained through artificial coloring, which is mainly used in the field of building decoration. It is mainly made of white or light-colored quartz sand that is artificially colored. It has the characteristics of uniform and bright colors. Products of different colors can be prepared according to needs. Artificial colored sand can be used in the field of construction, decoration or other fields.
[0003] Artificial colored sand can make the floor surface smoother and more translucent, improve the hardness and wear resistance of floor paint, and is suitable for floors in high-traffic areas to improve durability and safety. However, during the dyeing process, due to the different shapes of quartz sand and the difficulty in coloring, it is easy to affect the color permeability, color fastness and color uniformity of the quartz sand surface. In addition, the artificial colored sand applied on the ground is prone to gradual wear due to the passage of pedestrians and vehicles, and the color on the surface of the quartz sand is easily scraped off, affecting the service life of the artificial colored sand.
[0004] Therefore, how to prepare an artificial colored sand with good wear resistance, high color fastness, good color permeability and high color uniformity is a problem to be solved. Summary of the invention
[0005] In order to prepare an artificial colored sand with good wear resistance, high color fastness, good color permeability and high color uniformity, the present application provides an artificial colored sand and a preparation method thereof.
[0006] In the first aspect, the present application provides an artificial colored sand, which adopts the following technical solution: An artificial colored sand comprises quartz sand and a dyeing layer; The dyeing layer is prepared from a dyeing liquid, which contains the following raw materials in parts by weight: 80-100 parts of water-based acrylic resin, 180-220 parts of water, 8-10 parts of curing agent, 2-6 parts of dispersant, 30-40 parts of polyacrylamide modified dye, 1-5 parts of polycaprolactone coated thickener, 2-5 parts of plasticizer, 2-5 parts of silane coupling agent, 1-3 parts of weathering agent and 10-20 parts of wear-resistant filler.
[0007] By adopting the above technical scheme, the dyeing layer prepared by water-based acrylic resin is environmentally friendly and has good weather resistance and color stability. In combination with a weathering agent, it still has good color stability even when exposed to outdoor conditions for a long time. It also has good chemical corrosion resistance, can resist corrosion from acid and alkali substances, ensure color fastness, and improve the color fastness of artificial colored sand.
[0008] Water-based acrylic resin, polyacrylamide modified dye, and polycaprolactone coated thickener are matched, and the cross-linking effect of water-based polypropylene resin and polyacrylamide is utilized to improve the color uniformity of the dye in the water-based acrylic resin, and the color uniformity of the artificial colored sand is improved; and polycaprolactone is not easy to melt at room temperature, so the thickener is guaranteed to be in a coated state, and the water-based acrylic resin, under the dispersion conditions of the dispersant and polyacrylamide, ensures that the dye has a good color penetration effect on the surface of the quartz sand, and is not easily affected by excessive viscosity. The adhesion uniformity of the color on the surface of the quartz sand is improved, and the color permeability and color adhesion stability of the artificial colored sand are improved; and after being evenly mixed, the silane coupling agent and the plasticizer promote stable bonding between the dyeing layer and the quartz sand, ensure that the dye is stably attached to the surface of the quartz sand, and improve the color fastness of the artificial colored sand.
[0009] Water-based acrylic resin, polyacrylamide modified dye, plasticizer and wear-resistant filler are matched together, and the cross-linking bonding effect of water-based acrylic resin, polyacrylamide modified dye and plasticizer is utilized to make the dyeing layer have a higher cross-linking density, thereby improving the wear resistance of the dyeing layer; and the polyacrylamide around the dye has good wear resistance, and with the higher cross-linking density, the wear resistance of the dyeing layer is further improved; at the same time, with the dispersion filling effect of the wear-resistant filler, the wear resistance of the dyeing layer is further improved, and the color is protected from being easily worn, thereby improving the wear resistance of the artificial colored sand, and making the artificial colored sand laid on the ground have a higher color fastness.
[0010] Preferably, the polyacrylamide modified dye is prepared from a dye, a polycaprolactone melt and a polyacrylamide solution in a mass ratio of 1:0.1-0.2:0.1-0.2.
[0011] By adopting the above technical scheme, the viscosity of the polycaprolactone melt is utilized to attach polycaprolactone to the surface of the dye, and then the viscosity of the polyacrylamide solution is utilized to attach polyacrylamide to the surface of the dye; the dispersing effect of polyacrylamide is utilized to make the dye evenly dispersed in the dyeing liquid, so that the dye in the dyeing liquid is evenly distributed on the surface of the quartz sand, thereby improving the color uniformity of the artificial colored sand; when the dyeing liquid is heated for solidification, the polycaprolactone on the polyacrylamide modified dye attached to the surface of the quartz sand is gradually melted, further guiding the dye molecules to evenly reach various positions on the surface of the quartz sand, so that the surface of the quartz sand with uneven shape has better color uniformity, and the viscosity of the polycaprolactone is utilized to facilitate the stable adhesion of the dye to the surface of the quartz sand, thereby further improving the color fastness.
[0012] By utilizing the good flexibility, impact resistance and wear resistance of polycaprolactone and polyacrylamide, the wear resistance of the dye is improved, and the dye on the surface of the quartz sand is stably attached, thereby improving the wear resistance of the artificial colored sand and preventing the color from weakening due to wear. At the same time, polycaprolactone has a certain waterproof effect, which can protect the dye from being washed away by rain and becoming lighter in color, thereby improving the water resistance and color fastness of the artificial colored sand.
[0013] Preferably, the polycaprolactone coated thickener is prepared from polyvinyl alcohol particles and polycaprolactone melt in a mass ratio of 1:1-1.5.
[0014] By adopting the above technical scheme, the bonding effect of the polycaprolactone melt is utilized to achieve the coating of the polyvinyl alcohol particles. During the raw material mixing process of the dyeing liquid, the polyvinyl alcohol is coated by the polycaprolactone. The polycaprolactone is insoluble in water, so that the uniformity of the contact between the dyeing liquid and the quartz sand is not easily affected by excessive viscosity during the contact between the dyeing liquid and the quartz sand, thereby ensuring the permeability and uniformity of the color on the artificial colored sand. After the dye is evenly attached to the surface of the quartz sand, during the temperature rising and curing process, the polycaprolactone gradually melts and releases the polyvinyl alcohol. The water-soluble polyvinyl alcohol increases the viscosity, thereby improving the adhesion fastness of the dye on the surface of the quartz sand, thereby improving the color fastness of the artificial colored sand.
[0015] Preferably, the dispersant is composed of coconut amine polyoxyethylene ether and sodium polyacrylate in a mass ratio of 1:1-3.
[0016] By adopting the above technical scheme, the carboxyl group on sodium polyacrylate cooperates with the amide group in polyacrylamide to improve the dispersion effect of the dye. When the polyacrylamide is separated from the surface of the dye, the coconut amine polyoxyethylene ether and polycaprolactone cooperate with each other to further promote the uniform dispersion of the dye in the dyeing liquid, thereby improving the color distribution uniformity of the dyeing liquid.
[0017] Preferably, the plasticizer is composed of epoxy fatty acid ester.
[0018] By adopting the above technical scheme, the molecules of epoxy fatty acid ester contain epoxy groups, which have high reactivity and can chemically react with active groups such as carboxyl and hydroxyl groups in acrylic resin molecules to form stable chemical bonds, increase the interaction force between resin molecules, and improve the impact resistance and wear resistance of the dyeing layer.
[0019] Epoxy fatty acid esters also have good lubricity and dispersibility. When combined with polyacrylamide-modified dyes and dispersants, they can further improve the uniform dispersion of various substances in the dyeing solution and the uniformity of dye dispersion. At the same time, epoxy fatty acid esters and polycaprolactone are combined to have good water resistance, which can improve the water erosion resistance of artificial colored sand and ensure the color fastness of artificial colored sand to water erosion.
[0020] Preferably, the wear-resistant filler is composed of hydroxyl-modified polycarbonate, amino-modified silicon nitride particles and silicon dioxide particles in a mass ratio of 1:1-2:0.5-1.
[0021] By adopting the above technical scheme, hydroxyl-modified polycarbonate, amino-modified silicon nitride particles and silicon dioxide particles are matched, and polycarbonate, silicon nitride particles and silicon dioxide particles all have good strength and wear resistance, thereby improving the wear resistance of artificial colored sand, protecting the color for a long time, and not easily fading due to wear; and the hydroxyl groups on the surface of polycarbonate and the amino groups on the surface of silicon nitride particles can be cross-linked and bonded with water-based acrylic resin and polyacrylamide modified dyes, thereby improving the adhesion stability of wear-resistant fillers and dyes, and can also improve the cross-linking density of the dyeing layer. By using a higher cross-linking density, the wear resistance and color fastness of the artificial colored sand are further improved; silicon dioxide is combined with a silane coupling agent and quartz sand to further enhance the adhesion effect of the dyeing liquid on the surface of the quartz sand, and improve the dispersion uniformity and bonding stability of silicon dioxide, further improving the wear resistance and color fastness of the artificial colored sand.
[0022] Preferably, the hydroxy-modified polycarbonate is prepared from a polycarbonate and a polyethylene glycol solution in a mass ratio of 1:0.5-1.
[0023] By adopting the above technical scheme, polyethylene glycol is adhered to the surface of polycarbonate, and the bonding and cross-linking effect of polyethylene glycol with water-based acrylic resin and polyacrylamide modified dye is utilized to increase the cross-linking density of polycarbonate and water-based acrylic resin, and to increase the bonding stability between polycarbonate and dye, so that the artificial colored sand has better wear resistance; when subjected to wear, the wear resistance and dense cross-linking density of polycarbonate are utilized to further protect the dye from stably adhering to the surface of quartz sand, and the problem of color fastness change is not easily caused.
[0024] Preferably, the amino-modified silicon nitride particles are prepared by treating silicon nitride particles with an aminosulfonic acid solution.
[0025] By adopting the above technical scheme, the silicon nitride particles treated with aminosulfonic acid can increase the roughness and surface area of the silicon nitride particles, further increase the contact area between the silicon nitride particles and the water-based acrylic resin, and cooperate with the amino group to further improve the cross-linking effect, so that the dyeing layer has better wear resistance and higher color fastness.
[0026] In a second aspect, the present application provides a method for preparing artificial colored sand, using the following technical solution: A method for preparing artificial colored sand comprises the following steps: S1, quartz sand particles are pretreated with a citric acid solution, dried, and then the surface is evenly sprayed with a sodium polyacrylate solution, dried, and dispersed to obtain quartz sand; the mass ratio of quartz sand particles to sodium polyacrylate solution is 100:1-2; S2. Mix quartz sand and water-based acrylic resin particles and stir them evenly, then add dyeing liquid evenly, and solidify them at 60-65°C. The water-based acrylic resin and the dyeing liquid form a dyeing layer with an average thickness of 10-40 μm. After dispersion treatment, artificial colored sand is obtained.
[0027] By adopting the above technical scheme, the surface of the quartz sand particles is treated with citric acid to increase its surface area, which is convenient for loading the sodium polyacrylate solution and the dyeing liquid; the quartz sand is mixed with solid aqueous acrylic resin particles, and the mixing uniformity between the particles is high; finally, the dyeing liquid is evenly sprayed, and the bonding effect and dispersion effect of the dyeing liquid, the diversion effect of the sodium polyacrylate on the surface of the quartz sand, and the particle bridging effect of the aqueous acrylic resin particles are utilized to make the dyeing agent evenly reach the surface of quartz sand of different shapes, and the dyeing agent is evenly attached to the surface of the quartz sand, thereby improving the penetration wettability and dyeing uniformity of the dyeing liquid; finally, it is cured at 60-65°C, and after the polycaprolactone is hot-melted, the thickener is gradually released, which prompts the dyeing liquid to stably adhere to the surface of the quartz sand, and at the same time promotes the dyeing liquid to form a dyeing layer with a high degree of cross-linking, thereby improving the wear resistance and color fastness of the artificial colored sand.
[0028] Preferably, the polyacrylamide modified dye in the dyeing solution is prepared by the following method: The polycaprolactone melt is evenly sprayed on the surface of the dye, and after drying, the polyacrylamide solution is evenly sprayed, and after drying and dispersion, the polyacrylamide modified dye is obtained.
[0029] By adopting the above technical scheme, the prepared polyacrylamide modified dye forms a structure with polyacrylamide on the outside, polycaprolactone in the middle and the dyeing agent on the inside, thereby ensuring the dispersion effect of the dyeing agent in the dyeing liquid and the adhesion stability of the dyeing agent on the surface of quartz sand; and polycaprolactone has high transparency and is not easy to affect the color representation of the dyeing agent itself, so that the artificial colored sand has better color uniformity and color fastness.
[0030] In summary, this application has the following beneficial effects: 1. Water-based acrylic resin and polyacrylamide modified dyes are combined to utilize the cross-linking effect of water-based polyacrylamide and polyacrylamide to improve the color uniformity of the dye in the water-based acrylic resin and the color uniformity of the artificial colored sand; and the higher the degree of cross-linking, the better the wear resistance of the artificial colored sand, and at the same time, it has better color fastness.
[0031] 2. After the surface of the quartz sand particles is treated with citric acid, its surface area is increased to facilitate the loading of sodium polyacrylate solution and dyeing liquid; the quartz sand is mixed with solid aqueous acrylic resin particles, and the mixing uniformity between the particles is high. Finally, the dyeing liquid is evenly sprayed so that the dyeing agent evenly reaches the surface of quartz sand of different shapes, thereby improving the dyeing uniformity of the artificial colored sand. Finally, it is cured at 60-65°C. After the polycaprolactone is hot-melted, the thickener is gradually released, which prompts the dyeing liquid to stably adhere to the surface of the quartz sand, and at the same time promotes the dyeing liquid to form a dyeing layer with a high degree of cross-linking, thereby improving the wear resistance and color fastness of the artificial colored sand.
[0032] 3. The combination of polycaprolactone coated thickener, polyacrylamide modified dye and silane coupling agent utilizes the water resistance of polycaprolactone, the hydrophobic effect of silane coupling agent, and the high cross-linking effect of dye and water-based acrylic resin to improve the water resistance of artificial colored sand. Under rain erosion conditions, it still has good color fastness. DETAILED DESCRIPTION
[0033] The present application is further described in detail below with reference to the embodiments.
[0034] The following raw materials are all commercially available.
[0035] Preparation example of polyacrylamide modified dye Preparation Example 1: Polyacrylamide modified dye is prepared by the following method: 0.2 kg of polycaprolactone melt is evenly sprayed on the surface of 1 kg of dye. After drying, 0.2 kg of polyacrylamide solution is evenly sprayed. After drying, it is dispersed until the dye does not stick to each other to obtain a polyacrylamide modified dye. The dye is cobalt blue with an average particle size of 2 μm. The polycaprolactone melt is obtained by heating polycaprolactone to 60°C and completely melting it. The polyacrylamide solution is a 1% by mass aqueous solution of polyacrylamide.
[0036] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.1 kg of polycaprolactone melt is evenly sprayed on the surface of 1 kg of dye. After drying, 0.1 kg of polyacrylamide solution is evenly sprayed. After drying and dispersion, polyacrylamide modified dye is obtained. The dye is chrome yellow with an average particle size of 2 μm. The polycaprolactone melt is obtained by completely hot-melting polycaprolactone heated to 60°C. The polyacrylamide solution is a polyacrylamide aqueous solution with a mass fraction of 1%.
[0037] The dyes used in the above-mentioned Preparation Examples 1 and 2 include, but are not limited to, cobalt blue and chrome yellow.
[0038] Preparation Example of Polycaprolactone Coated Thickener Preparation Example 3: Polycaprolactone coated thickener is prepared by the following method: 1.5 kg of polycaprolactone melt was evenly sprayed on the surface of 1 kg of polyvinyl alcohol particles. The average particle size of the polyvinyl alcohol particles was 20 μm. The polycaprolactone melt was obtained by heating the polycaprolactone to 60° C. and completely melting it. The polycaprolactone coated thickener was obtained by drying and dispersing the polyvinyl alcohol particles until they did not stick to each other and agglomerate.
[0039] Preparation Example 4: This preparation example differs from Preparation Example 3 in that: 1 kg of polycaprolactone melt was evenly sprayed on the surface of 1 kg of polyvinyl alcohol particles. The average particle size of the polyvinyl alcohol particles was 20 μm. The polycaprolactone melt was obtained by heating polycaprolactone to 60° C. and completely melting it. After drying and dispersion, a polycaprolactone coated thickener was obtained.
[0040] Preparation example of wear-resistant filler Preparation Example 5: Wear-resistant filler is prepared by the following method: 1 kg of polyethylene glycol solution is uniformly sprayed on the surface of 1 kg of polycarbonate, wherein the average particle size of the polycarbonate is 500 nm, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 10%, and the polyethylene glycol is polyethylene glycol 2000, and then dried and dispersed until the polycarbonate does not stick to each other and agglomerate, thereby obtaining a hydroxy-modified polycarbonate; 1 kg of silicon nitride particles are placed in 10 kg of aminosulfonic acid solution, the average particle size of the silicon nitride particles is 1 μm, and the aminosulfonic acid solution is an aminosulfonic acid aqueous solution with a mass fraction of 1%, and ultrasonic dispersion is performed at 20 kHz for 10 minutes, and the silicon nitride particles are separated by filtration, and then air-dried and dispersed until the silicon nitride particles do not stick to each other and agglomerate, to obtain amino-modified silicon nitride particles; 1 kg of hydroxyl-modified polycarbonate, 2 kg of amino-modified silicon nitride particles and 1 kg of silicon dioxide particles were mixed and stirred uniformly, wherein the average particle size of the silicon dioxide particles was 1 μm, to obtain a wear-resistant filler, which did not adhere to or agglomerate with each other.
[0041] Preparation Example 6: This preparation example differs from Preparation Example 5 in that: 0.5 kg of polyethylene glycol solution is uniformly sprayed on the surface of 1 kg of polycarbonate, the average particle size of the polycarbonate is 500 nm, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 10%, and the polyethylene glycol is polyethylene glycol 2000, and then dried and dispersed to obtain a hydroxyl-modified polycarbonate; 1 kg of silicon nitride particles are placed in 10 kg of aminosulfonic acid solution, the average particle size of the silicon nitride particles is 1 μm, and the aminosulfonic acid solution is an aminosulfonic acid aqueous solution with a mass fraction of 1%, and ultrasonic dispersion is performed at 20 kHz for 10 minutes, and the silicon nitride particles are separated by filtration, and air-dried to obtain amino-modified silicon nitride particles; 1 kg of hydroxyl-modified polycarbonate, 1 kg of amino-modified silicon nitride particles and 0.5 kg of silicon dioxide particles were mixed and stirred uniformly, wherein the average particle size of the silicon dioxide particles was 1 μm, to obtain a wear-resistant filler.
[0042] Example of preparation of staining solution Preparation Example 7: The dye solution was prepared by the following method: Preparation: 90kg of water-based acrylic resin, 200kg of water, 9kg of curing agent, 4kg of dispersant, 35kg of polyacrylamide modified dye, 3kg of polycaprolactone coated thickener, 3kg of plasticizer, 4kg of silane coupling agent, 2kg of weathering agent, and 15kg of wear-resistant filler; the curing agent is composed of diethylenetriamine and polyetheramine in a mass ratio of 1:0.5, and the polyetheramine is polyetheramine T403; the dispersant is composed of coconut amine polyoxyethylene ether and sodium polyacrylate in a mass ratio of 1:2; the polyacrylamide modified dye is the polyacrylamide modified dye prepared in Preparation Example 1; the polycaprolactone coated thickener is the polycaprolactone coated thickener prepared in Preparation Example 3; the plasticizer is epoxy fatty acid ester; the silane coupling agent is silane coupling agent KH-570; the weathering agent is ultraviolet absorber UV-531; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 5; Weigh water-based acrylic resin and water, mix and stir until the water-based acrylic resin is completely dissolved, then add dispersant, polyacrylamide modified dye, polycaprolactone coated thickener, plasticizer, wear-resistant filler, mix and stir evenly, keep the temperature at 30°C, finally add silane coupling agent and weathering agent, mix and stir evenly, and package to obtain material A; The curing agent is material B; when it is used, material A and material B are mixed evenly and used immediately to obtain a dyeing solution.
[0043] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: Preparation: 80g water-based acrylic resin, 180kg water, 8kg curing agent, 2kg dispersant, 30kg polyacrylamide modified dye, 1kg polycaprolactone coated thickener, 2kg plasticizer, 2kg silane coupling agent, 1kg weathering agent, 10kg wear-resistant filler; the dispersant is composed of coconut amine polyoxyethylene ether and sodium polyacrylate in a mass ratio of 1:1; the polyacrylamide modified dye is the polyacrylamide modified dye prepared in Preparation Example 2; the polycaprolactone coated thickener is the polycaprolactone coated thickener prepared in Preparation Example 4; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 6.
[0044] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: Preparation: 100kg water-based acrylic resin, 220kg water, 10kg curing agent, 6kg dispersant, 40kg polyacrylamide modified dye, 5kg polycaprolactone coated thickener, 5kg plasticizer, 5kg silane coupling agent, 3kg weathering agent, 20kg wear-resistant filler; the dispersant is composed of coconut amine polyoxyethylene ether and sodium polyacrylate in a mass ratio of 1:3; the polyacrylamide modified dye is the polyacrylamide modified dye prepared in Preparation Example 1; the polycaprolactone coated thickener is the polycaprolactone coated thickener prepared in Preparation Example 3; the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 5. Example
[0045] Embodiment 1: A kind of artificial colored sand: Includes quartz sand and dyeing layers; The preparation method is as follows: S1, placing 100kg of quartz sand particles in 200kg of citric acid solution, the average particle size of the quartz sand particles is 1mm, the citric acid solution is a citric acid aqueous solution with a concentration of 1%, stirring at a speed of 80r / min for 30min, and then filtering and separating the quartz sand particles, the citric acid solution is ensured to have a concentration of 1% for recycling, and the pretreatment is completed; after the surface is dried, 2kg of sodium polyacrylate solution is evenly sprayed, the sodium polyacrylate solution is a sodium polyacrylate aqueous solution with a mass fraction of 1%, and after drying, quartz sand is obtained, and the quartz sands do not stick to each other and agglomerate; S2. Mix and stir quartz sand and water-based acrylic resin particles evenly, the average particle size of the water-based acrylic resin particles is 80 μm, and then evenly add the dyeing solution prepared in Preparation Example 7. Curing at 60°C for 5 hours, the water-based acrylic resin particles and the dyeing solution form a dyeing layer, the average thickness of the dyeing layer is 20 μm, and disperse until the quartz sand does not stick to each other and agglomerate, thereby obtaining artificial colored sand.
[0046] Embodiment 2: This embodiment differs from Embodiment 1 in that: The preparation method is as follows: S1, placing 100kg of quartz sand particles in 200kg of citric acid solution, the average particle size of the quartz sand particles is 1mm, the citric acid solution is a citric acid aqueous solution with a concentration of 1%, stirring at a speed of 80r / min for 30min, then filtering and separating the quartz sand particles, the citric acid solution is ensured to have a concentration of 1% for recycling, and the pretreatment is completed; after the surface is dried, 1kg of sodium polyacrylate solution is evenly sprayed, and dried to obtain quartz sand; S2. Mix and stir quartz sand and water-based acrylic resin particles evenly, the average particle size of the water-based acrylic resin particles is 80 μm, and then evenly add the dyeing solution prepared in Preparation Example 8. Curing at 60°C for 5 hours, the water-based acrylic resin particles and the dyeing solution form a dyeing layer, the average thickness of the dyeing layer is 10 μm, and disperse until the quartz sand does not stick to each other and agglomerate, thereby obtaining artificial colored sand.
[0047] Embodiment 3: This embodiment differs from Embodiment 1 in that: The preparation method is as follows: S1, placing 100kg of quartz sand particles in 200kg of citric acid solution, the average particle size of the quartz sand particles is 1mm, the citric acid solution is a citric acid aqueous solution with a concentration of 1%, stirring at a speed of 80r / min for 30min, then filtering and separating the quartz sand particles, the citric acid solution is ensured to have a concentration of 1% for recycling, and the pretreatment is completed; after the surface is dried, 3kg of sodium polyacrylate solution is evenly sprayed, and dried to obtain quartz sand; S2. Mix and stir quartz sand and water-based acrylic resin particles evenly, the average particle size of the water-based acrylic resin particles is 80 μm, and then evenly add the dyeing solution prepared in Preparation Example 9, and cure at 65°C for 5 hours. The water-based acrylic resin particles and the dyeing solution form a dyeing layer with an average thickness of 40 μm. Disperse until the quartz sand does not stick to each other and agglomerate, thereby obtaining artificial colored sand.
[0048] Embodiment 4: This embodiment differs from Embodiment 1 in that: No polycaprolactone melt is added in the preparation process of the polyacrylamide modified dye in the raw material.
[0049] Embodiment 5: This embodiment differs from Embodiment 1 in that: No coconut amine polyoxyethylene ether was added as dispersant in the raw materials.
[0050] Embodiment 6: This embodiment differs from Embodiment 1 in that: The wear-resistant filler in the raw materials is replaced by polycarbonate of equal mass for hydroxy-modified polycarbonate, and the wear-resistant filler is replaced by silicon nitride particles of equal mass for amino-modified silicon nitride particles.
[0051] Embodiment 7: This embodiment differs from Embodiment 1 in that: The quartz sand in S1 was not treated with citric acid solution and sodium polyacrylate solution.
[0052] Embodiment 8: This embodiment differs from Embodiment 1 in that: No water-based acrylic resin particles were added to S2.
[0053] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The polyacrylamide modified dye is replaced by a dye of equal quality in the raw materials.
[0054] Comparative Example 2: The difference between this comparative example and Example 1 is that: The polycaprolactone coated thickener is replaced by a thickener of equal mass in the raw materials.
[0055] Performance testing 1. Wear resistance test Artificial colored sand was prepared by the methods of Examples 1-8 and Comparative Examples 1-2, respectively. 10 kg of artificial colored sand was stirred at a high speed of 2000 r / min for 1 hour, and the weight of the debris produced after stirring was filtered and weighed. The debris particle size was less than 100 μm and the data was recorded. A small debris weight indicates good wear resistance and high color fastness.
[0056] 2. Water resistance test Artificial colored sand was prepared by the methods of Examples 1-8 and Comparative Examples 1-2, respectively. The artificial colored sand was immersed in water. When the water was dyed, it was determined to be discolored, and the fading time was recorded. The color of the water dyeing was based on Example 1. The subsequent examples and comparative examples were based on the color of the water dyeing of Example 1. The color of the water dyeing of Example 1 was determined to be discolored, and the fading time was recorded. The time when the fading started was used to characterize the wear resistance. The longer the time, the better the water fastness.
[0057] 3. Color uniformity detection Artificial colored sand was prepared by the methods of Examples 1-8 and Comparative Examples 1-2, and the surface of 1 kg of artificial colored sand was observed to be uniformly dyed. The uniformity of dyeing was observed and then scored. The scoring criteria were as follows: uniform color and bright color 10 points → uneven color, dark and light colors, and a large difference in depth 0 point.
[0058] Table 1 Performance test table
[0059] It can be seen from Examples 1-3 and Table 1 that the artificial colored sand prepared in the present application has good wear resistance and color fastness, is not easy to fade when soaked in water, has good water resistance, and has good dyeing uniformity.
[0060] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that no polycaprolactone melt was added during the preparation of the polyacrylamide-modified dye in the raw material of Example 4. Compared with Example 1, the weight of the artificial colored sand crumbs prepared in Example 4 is higher than that in Example 1, the fading time is shorter than that in Example 1, and the score is lower than that in Example 1; this indicates that the addition of polycaprolactone can not only promote the more stable adhesion of the dye on the surface of quartz sand and improve the color fastness, but also polycaprolactone is water-resistant, which can improve the water fastness of the artificial colored sand, and at the same time can promote the uniform dispersion of the dye on the surface of quartz sand and improve the dyeing uniformity.
[0061] In Example 5, no dispersant was added to the raw materials of coconut amine polyoxyethylene ether. Compared with Example 1, the score of artificial colored sand prepared in Example 5 was lower than that in Example 1, indicating that coconut amine polyoxyethylene ether and polycaprolactone cooperated with each other to further promote the uniform dispersion of the dye in the dyeing liquid and improve the color distribution uniformity of the dyeing liquid.
[0062] In Example 6, the wear-resistant filler in the raw materials is replaced by hydroxy-modified polycarbonate with an equal mass of polycarbonate, and the amino-modified silicon nitride particles are replaced by an equal mass of silicon nitride particles. Compared with Example 1, the weight of the artificial colored sand crumbs prepared in Example 6 is higher than that in Example 1, the fading time is shorter than that in Example 1, and the score is lower than that in Example 1; this indicates that the hydroxy-modified polycarbonate and the amino-modified silicon nitride particles can be cross-linked with water-based acrylic resin and polyacrylamide-modified dyes to improve the density of the dyeing layer, thereby improving the wear resistance and color fastness of the artificial colored sand; and utilizing its dispersion effect to improve the color uniformity of the artificial colored sand.
[0063] In Example 7S1, the quartz sand has not been treated with citric acid solution and sodium polyacrylate solution. Compared with Example 1, the weight of the artificial colored sand fragments prepared in Example 7 is higher than that in Example 1, the fading time is shorter than that in Example 1, and the score is lower than that in Example 1; this indicates that the quartz sand treated with citric acid solution and sodium polyacrylate solution has a larger surface area, which is convenient for adhering to the dyeing liquid and facilitating the uniform dispersion of the dye on the surface of the quartz sand, thereby improving the color uniformity and color fastness of the artificial colored sand, and at the same time can also improve the bonding effect between the quartz sand and the dyeing liquid, and improve the wear resistance and color fastness.
[0064] In Example 8S2, no water-based acrylic resin particles were added. Compared with Example 1, the weight of the artificial colored sand fragments prepared in Example 8 was higher than that in Example 1, the fading time was shorter than that in Example 1, and the score was lower than that in Example 1; this indicates that the granular structure of the water-based acrylic resin particles can be evenly mixed with the quartz sand. With the addition of the dyeing liquid, the diversion effect of the water-based acrylic resin particles and the dissolution effect of the water-based acrylic resin are utilized to further improve the bonding effect of the dyeing liquid and the quartz sand, thereby improving the wear resistance and color fastness of the artificial colored sand and at the same time improving the dyeing uniformity.
[0065] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that the polyacrylamide modified dye is replaced with a dye of equal mass in the raw material of Comparative Example 1. Compared with Example 1, the weight of the artificial colored sand chips prepared in Comparative Example 1 is higher than that in Example 1, the fading time is shorter than that in Example 1, and the score is lower than that in Example 1; this indicates that polyacrylamide has a good dispersion effect, which can make the dye evenly dispersed in the dyeing liquid, thereby improving the dyeing effect of quartz sand, and cooperates with the cross-linking effect between polyacrylamide and the water-based acrylic resin to improve the wear resistance and color fastness of the dyeing layer.
[0066] In Comparative Example 2, the polycaprolactone coated thickener is replaced with a thickener of equal mass in the raw materials. Compared with Example 1, the weight of the artificial colored sand crumbs prepared in Comparative Example 2 is higher than that in Example 1, the fading time is shorter than that in Example 1, and the score is lower than that in Example 1; this indicates that the direct addition of the thickener is likely to increase the viscosity of the dyeing liquid, affecting the uniform dispersion effect of the dyeing liquid in the quartz sand, and the direct addition of the thickener is likely to lead to uneven distribution of the dyeing layer, resulting in problems such as thicker local dyeing layers and thinner local dyeing layers. During the friction process, it is easy to be worn, affecting the wear resistance and color fastness of the artificial colored sand; at the same time, polycaprolactone has certain water resistance, which can improve the water resistance and color fastness of the artificial colored sand.
Claims
1. An artificial colored sand, characterized in that: Includes quartz sand and dyeing layers; The dyeing layer is prepared from a dyeing liquid, which contains the following raw materials in parts by weight: 80-100 parts of water-based acrylic resin, 180-220 parts of water, 8-10 parts of curing agent, 2-6 parts of dispersant, 30-40 parts of polyacrylamide modified dye, 1-5 parts of polycaprolactone coated thickener, 2-5 parts of plasticizer, 2-5 parts of silane coupling agent, 1-3 parts of weathering agent and 10-20 parts of wear-resistant filler.
2. The artificial colored sand according to claim 1, characterized in that: The polyacrylamide modified dye is prepared from a dye, a polycaprolactone melt and a polyacrylamide solution in a mass ratio of 1:0.1-0.2:0.1-0.
2.
3. The artificial colored sand according to claim 1, characterized in that: The polycaprolactone coated thickener is prepared from polyvinyl alcohol particles and polycaprolactone melt in a mass ratio of 1:1-1.
5.
4. The artificial colored sand according to claim 1, characterized in that: The dispersant consists of coconut amine polyoxyethylene ether and sodium polyacrylate in a mass ratio of 1:1-3.
5. The artificial colored sand according to claim 1, characterized in that: The plasticizer is composed of epoxy fatty acid ester.
6. The artificial colored sand according to claim 1, characterized in that: The wear-resistant filler is composed of hydroxyl-modified polycarbonate, amino-modified silicon nitride particles and silicon dioxide particles in a mass ratio of 1:1-2:0.5-1.
7. The artificial colored sand according to claim 6, characterized in that: The hydroxyl-modified polycarbonate is prepared from a polycarbonate and a polyethylene glycol solution in a mass ratio of 1:0.5-1.
8. The artificial colored sand according to claim 6, characterized in that: The amino-modified silicon nitride particles are prepared by treating silicon nitride particles with aminosulfonic acid solution.
9. A method for preparing artificial colored sand according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, quartz sand particles are pretreated with a citric acid solution, dried, and then the surface is evenly sprayed with a sodium polyacrylate solution, dried, and dispersed to obtain quartz sand; the mass ratio of quartz sand particles to sodium polyacrylate solution is 100:1-3; S2. Mix quartz sand and water-based acrylic resin particles and stir them evenly, then add dyeing liquid evenly, and solidify them at 60-65°C. The water-based acrylic resin and the dyeing liquid form a dyeing layer with an average thickness of 10-40 μm. After dispersion treatment, artificial colored sand is obtained.
10. The method for preparing artificial colored sand according to claim 9, characterized in that: The polyacrylamide modified dye in the dyeing solution is prepared by the following method: The polycaprolactone melt is evenly sprayed on the surface of the dye, and after drying, the polyacrylamide solution is evenly sprayed, and after drying and dispersion, the polyacrylamide modified dye is obtained.